Identification of α-glucosidase inhibitors from cyclocarya paliurus tea leaves using UF-UPLC-Q/TOF-MS/MS and molecular docking. Issue 4 (13th March 2019) - Ning, Zi-wan; Zhai, Li-xiang; Huang, Tao; Peng, Jiao; Hu, Die; Xiao, Hai-tao; Wen, Bo; Lin, Cheng-yuan; Zhao, Ling; Bian, Zhao-xiang
Abstract : 11 potential α-glucosidase inhibitors in leaves of Cyclocarya paliurus were quickly identified by UF-UPLC-Q/TOF-MS/MS, and their inhibitory activities were verified in vitro and in vivo, as well as docked with homology model. Abstract : Leaves of Cyclocarya paliurus (CP) have a potential antihyperglycemic effect, but its active compositions responsible for the beneficial properties remain unclear. The CP extract exhibited remarkable α-glucosidase inhibitory activity with an IC50 value of 31.5 ± 1.05 μg mL −1, much lower than that of the positive control acarbose (IC50 = 296.6 ± 1.06 μg mL −1 ). To identify the specific α-glucosidase inhibitors from the CP extract, affinity ultrafiltration coupled with ultra-performance liquid chromatography and quadrupole-time-of-flight mass spectrometry (UF-UPLC-Q/TOF-MS/MS) was developed and 11 potential α-glucosidase inhibitors from CP extract were identified. In vitro α-glucosidase inhibitory assay verified that quercetin-3- O -glucuronide, kaempferol-3- O -rhamnoside, quercetin, kaempferol, asiatic acid and genistein were primarily responsible for the α-glucosidase inhibitory activity of the CP extract. Further, a hypoglycemia test also verified that these α-glucosidase inhibitors had the potential to reduce post-prandial hyperglycaemia in C57BL/6 mice. Moreover, the molecular docking study revealed that these identified α-glucosidase inhibitors more easily occupy the active sites of α-glucosidase than does the positive control acarbose. These findings suggest the CP tea leaves are the potential source of a hypoglycaemic agent.